A thermodynamic comparison of membrane-assisted processes for hydrogen production with integrated CO2 capture - Pouw, S.; Bevers, M.; Gallucci, F.; Van Sint Annaland, M. (Frontiers in Chemical Engineering, 2024)
The energy efficiency of two novel process designs for the production of ultra-pure hydrogen with simultaneous capture of CO2 using CH4 as the feedstock, namely membrane-assisted chemical looping reforming (MA-CLR) and membrane-assisted sorption-enhanced reforming (MA-SER) has been compared. The modelling of the integrated network for mass and heat balances has been carried out using the ASPEN® Plus V10 process simulation tool to quantify the benefits and disadvantages of integrating hydrogen perm-selective membranes with either chemical looping or sorption-enhanced reforming. The evaluation of the MA-CLR process is carried out for a range of the following operating conditions: 10 < pR < 60 bar, 500 < TR < 900 C, and 1.5 < H2O/CH4 < 3.0. On the other hand, for the MA-SER process the operation ranges of 1.0 < pR < 10 bar, 400 < TR < 900 C, and 2.5 < H2O/CH4 < 4.0 were considered. Within the operation window of the MA-SER process, no carbon formation is observed, as any carbon present in the system reacts with CaO in the form of CO2. However, in the case of the MA-CLR process, carbon formation can occur during the pre-reforming stage, particularly at low H2O/CH4 ratios. In terms of hydrogen yield, energy utilization and carbon capture, the MA-CLR outperforms the MA-SER plant. However, the MA-SER plant offers certain advantages over the MA-CLR system, such as a pure CO2 product stream and lower reactor design temperatures. In the MA-CLR system, a carbon capture rate of 99.8% and a hydrogen product yield of 74.4% are achieved, whereas the MA-SER plant achieves a carbon capture rate of 98.5% and a hydrogen product yield of 69.7%.